Preparation and electrochemical noise characteristics of graphene-composite coating with different contents of 7A52 aluminum alloy matrix - SUN Xiao-feng; HAO Song-song; SONG Wei; LI Zhan-ming; SHI Yu-peng (工程科学学报)
In the harsh marine environment, the traditional aluminum alloy coating has difficulty meeting the requirements of use, which can affect equipment performance. The traditional coating and a modified graphene composite were prepared with a base of 7A52 aluminum alloy, which has excellent anticorrosive properties. Then, the electrochemical noise was recorded to monitor the initial corrosion process of the modified graphene coating in 3.5% NaCl solution. By time-domain, statistical time-domain, Fourier transform, and frequency-domain analyses, the corrosion process was studied in coatings with different graphene-composite contents. Based on the change in the electrochemical noise parameters of the coating corrosion conditions, the graphene content that exhibited the best anti-corrosion performance was determined. The results reveal that for different levels of modified graphene, the electrochemical noise of the coatings differs at certain times. When the graphene coating is corroded, the current potential change process experiences a fluctuation range from small to large and the fluctuation range decreases. It is found that the AC impedance of the coating in the high-frequency region increases with increased modified graphene content. After adding modified graphene to the coating, the corrosion potential of the coating shifts significantly, the corrosion current density decreases, and the corrosion resistance of the coating is significantly increased. After immersion in 3.5% NaCl solution, pits of various severities appear on the aluminum alloy surface, whereas only a small number of pits appear on a 1% graphene coating. By combining the AC impedance results, the polarization curves, and the corrosion morphology of the aluminum alloy surface, the best coating corrosion resistance was observed to occur when the graphene content was 1%.